The Principal's Strategy for Fostering Morals and Worship Culture at Taruna Islamic Elementary School in Surabaya - Nasiri (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2023)
The principal is the educational leader at the school level and is responsible for the progress and decline of the school they lead. They are required to possess management and leadership skills to develop and advance their school effectively, efficiently, independently, productively, and accountably. The topic, "The Principal's Strategy in Fostering School Climate and Culture at Taruna Surabaya Islamic Elementary School (SDI)," is "The Principal's Strategy in Fostering School Climate and Culture at Taruna Surabaya Islamic Elementary School (SDI)," this study aims to uncover the principal's strategy in fostering school climate and culture at SDI Taruna Surabaya, along with the supporting and inhibiting factors. To address this issue, the following research techniques were used: 1) observation, used to determine the condition of SDI Taruna Surabaya and its activities; 2) interviews, used to gather data related to the principal's strategy in fostering school climate and culture at SDI Taruna Surabaya, along with the supporting and inhibiting factors; 3) documentation, used to obtain data, particularly related to the various instruments and test results used at SDI Taruna; and 4) focus group discussions to validate research findings and seek solutions to existing problems. Based on the formulation of the problem and by using data collection techniques, the results obtained are: 1) Strategies used to improve the quality of learning, which can be identified by researchers include: the implementation of an adaptive curriculum, boosting school achievement (students and teachers), involvement of the surrounding community and utilization of local potential, provision of infrastructure or service facilities, and establishing cooperation with external parties. 2) Several supporting factors are: the existence of good cooperation with teachers and educational staff based on their competence, discipline of the SDI Taruna academic community, adequate facilities and infrastructure, cooperative students in accepting school regulations, extracurricular activities, cooperation networks with external parties, support from the surrounding community. 3) The obstacles faced include: when there is an opportunity for students to participate in activities outside the area because of their competence, sometimes their parents do not allow it. Some do not have the funds for their children's pocket money, some because of psychological objections, and some for other reasons.